Pengantar Jurnal - Dina Y Sulaeman; M. Khoirul Malik; R. Widya Setiabudi Sumadinata (Indonesia Center for Middle East Studies, 2017)
In this file there are 4 introductory articles of Jurnal ICMES, namely: Middle East in International Political Economy Perspective by Dina Yulianti The Middle East Studies and Foreign Political Orientation of the Republic of Indonesia by R. Widya Setiabudi Sumadinata The Role of Media in Shaping the Public Opinions Concerning Middle East Issues by M. Khoirul Malik Middle East in the Hegemony of the United States by Kiki Mikail